Peranan Guru Pendidikan Agama Kristen Dalam Membangun Karakter Kristiani Siswa - Budimani Telaumbanua (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to determine whether Christian religious education teachers carry out their role in building Christian character of students at SD Negeri 071012 Hiligodu. This study used descriptive qualitative method. Descriptive method is a method in examining the status of a group of humans, an object, a condition, a system of thought or a present situation. The subjects of this study were students of SD Negeri 071012 Hiligodu with a total of 60 people. From the research carried out obtained hypothesis testing with significant (a) 0.05 or 0.95% variable X is known to be 0.436. This, there is the role of Christian religious education teachers in developing Christian character of students in SD Negeri 071012 Hiligodu academic year 2016/2017 but the Christian religious education teachers in SD Negeri 071012 Hiligodu academic year 2016/2017 have not fully implemented their roles. This is evident in the answer to variable Y where there are still answers c and d. The main problem is not fully implemented the role of Christian education teachers, namely students do not follow the rules of the school. In this case, it has been proven in the answer to variable Y there are still answers c and d. Christian religious education teachers have carried out their duties, however, students are unable to implement it so that good character is expected to be a Christian religious education teacher who needs to be rebuilt. Keywords: The Role of Teachers, Christian Characters Abstrak: Penelitian ini bertujuan untuk Untuk mengetahui apakah guru pendidikan agama Kristen menjalankan perannya dalam membangun karakter Kristiani siswa di SD Negeri 071012 Hiligodu. Penelitian ini menggunakan metode deskriptif kualitatif. Metode deskriptif merupakan suatu metode dalam meneliti status sekelompok manusia, suatu objek, suatu kondisi, suatu sistem pemikiran atau suatu keadaan sekarang. Subjek penelitian ini adalah siswa/siswi SD Negeri 071012 Hiligodu sejumlah 60 orang. Dari penelitian yang dilaksanakan diperoleh Uji hipotesis dengan signifikan (a) 0,05 atau 0,95% variabel X diketahui sebesar 0,436. Hal ini, terdapat peranan guru pendidikan agama Kristen dalam membangun karakter Kristiani siswa di SD Negeri 071012 Hiligodu Tahun Pelajaran 2016/2017 namun Guru pendidikan agama Kristen di SD Negeri 071012 Hiligodu Tahun Pelajaran 2016/2017 belum sepenuhnya melaksanakan peranannya. Hal ini, terbukti pada jawaban variabel Y dimana masih ada jawaban c dan d. Masalah utama tidak sepenuhnya terlaksana peranan guru pendidikan agama Kristen, yakni siswa kurang mengikuti aturan sekolah. Dalam hal ini, sudah terbukti pada jawaban variabel Y masih ada jawaban c dan d. Guru pendidikan agama Kristen sudah melaksanakan tugasnya namun, siswa tidak mampu melaksanakannya sehingga karakter yang baik diharapkan guru pendidikan agama Kristen masih perlu dibangun kembali. Kata kunci: Peran Guru, Karakter Kristiani